Chemical Modeling Of Calcium Sulphate Solubility In Hydrometallurgical Process Solutions - G. Azimi (The Minerals, Metals and Materials Society, 2006)
Calcium sulphate precipitation, mainly as gypsum, during neutralization of acidic hydrometallurgical process solutions can lead to excessive scaling problems. In this work, a self-consistent fundamental chemical model is presented based on the OLI software platform. The model employs the new Mixed Solvent Electrolyte (MSE) activity coefficient model of OLI. A thermodynamic database has been developed and calibrated on experimental data from metal sulphate solutions. The model predicts very well the solubility of calcium sulphate within a wide temperature range and can be used to assess the scaling potential of a particular process stream composition. The effect of temperature, acidity, and divalent metal concentration on the solubility of calcium sulphate in multi-component process streams is also simulated and discussed.